National Conflict in Czechoslovakia : the Making and Remaking of a State, 1918-1987. - Leff, Carol Skalnik (Princeton legacy library., 2014)
Czechoslovak domestic politics, including the long-standing policy dilemmas stemming from the so-called Slovak question, are usually approached from a historical standpoint. Here Carol Leff views the subject from a fresh analytic perspective. The Slovaks' dissatisfaction with their status in the constitutional order has dogged Czechoslovakia from the country's inception after World War I, and the substantial Slovak minority (now about one-third of the population) has recurrently complicated the state's struggle for self-definition, stability, and even survival. Professor Leff establishes a.